1999
DOI: 10.1016/s0735-1097(99)00231-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of stress/rest myocardial perfusion tomography, dipyridamole and dobutamine stress echocardiography for the detection of coronary disease in hypertensive patients with chest pain and positive exercise test

Abstract: This study shows that stress echo in patients with hypertension yields a satisfactory diagnostic accuracy for identifying significant epicardial CAD. Our results indicate that dobutamine might be superior to dipyridamole. The low specificity of myocardial scintigraphy probably relates to the fact that this method traces perfusion abnormalities, not necessarily caused by epicardial CAD, possibly due to microvascular disease and not causing obvious wall motion abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
62
0
1

Year Published

2000
2000
2006
2006

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(63 citation statements)
references
References 24 publications
0
62
0
1
Order By: Relevance
“…The presence of hypertension may cloud the diagnosis of CAD because chest pain and dyspnea, as well as stress-induced ST-segment changes, may be due to hypertensive heart disease even in the absence of CAD. However, although stress echocardiography has been shown to improve the diagnosis of CAD in hypertensive patients, [1][2][3] its value in prognostic evaluation is unclear.…”
mentioning
confidence: 99%
“…The presence of hypertension may cloud the diagnosis of CAD because chest pain and dyspnea, as well as stress-induced ST-segment changes, may be due to hypertensive heart disease even in the absence of CAD. However, although stress echocardiography has been shown to improve the diagnosis of CAD in hypertensive patients, [1][2][3] its value in prognostic evaluation is unclear.…”
mentioning
confidence: 99%
“…Very low (24%) specificity of exercise ECG in hypertensive patients was reported by Senior et al 3 In the group of hypertensive subjects with positive exercise stress test evaluated by Fragasso et al, 9 significant coronary artery disease was present in only 56%. This study confirms that specificity of exercise ECG in hypertensive subjects without previous myocardial infarction is quite low indeed.…”
Section: Discussionmentioning
confidence: 86%
“…Pepi et al 16 found that in hypertensive patients left ventricular wall motion abnormalities evoked by maximal bicycle exercise are 93% sensitive and 100% specific for significant coronary stenosis. Fragasso et al 9 reported on the high specificity of both dobutamine and dipyridamole in hypertensive patients with positive exercise ECG (80% and 91%). Zouridakis et al 17 who analysed a group of 18 hypertensive patients with normal coronary arteries and frequent (59%) positive Thallium SPECT result found normal left ventricular wall motion during dobutamine echocardiography in all cases.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it may very well be that ST depression that does not concur with angiographic findings or with other diagnostic modalities represents ST depression caused by microvascular abnormalities. [23][24][25] By following that line of reasoning, the reported low sensitivity of ECG investigations may be ready for revision by newer techniques that can measure flow at the tissue level (MRI, positron emission tomography).…”
Section: Boon Et Al Silent Ischemia In Hypertension 477mentioning
confidence: 99%